Applied Psychology. The Case of the Baer, Wolf and Risley Prescriptions for Applied Behavior Analysis (2014)
Baer, Wolf and Risley, members of the group that promoted the creation of the Journal of Applied Behavior Analysis, offered in its first issue a detailed series of ‘prescriptions’ that characterized the way research and research articles would be conceived as adequate to the applied field by the journal editors. Their ‘prescriptions’ have been largely cited, becoming a sign of authors’ identification with the journal policy, and widely influencing the structure and topics of this specialized literature.